2010
DOI: 10.1525/mp.2010.28.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Entrainment: Foundations of Coordinated Rhythmic Movement

Abstract: Entrainment has been studied in a variety of contexts including music perception, dance, verbal communication and motor coordination more generally. Here we seek to provide a unifying framework that incorporates the key aspects of entrainment as it has been studied in these varying domains. We propose that there are a number of types of entrainment that build upon pre-existing adaptations that allow organisms to perceive stimuli as rhythmic, to produce periodic stimuli, and to integrate the two using sensory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
239
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(246 citation statements)
references
References 80 publications
(119 reference statements)
2
239
0
5
Order By: Relevance
“…In human beings, the firing frequency of auditory neurons when receiving an external rhythmic stimulus influences the firing frequency of motor neurons, causing over time a coordinated movement (Thaut et al, 2015 p. 2). This resonates with the model of entrainment proposed by Phillips-Silver et al (2010), according to whom entrainment is composed of three phases:…”
Section: When To Movesupporting
confidence: 75%
See 1 more Smart Citation
“…In human beings, the firing frequency of auditory neurons when receiving an external rhythmic stimulus influences the firing frequency of motor neurons, causing over time a coordinated movement (Thaut et al, 2015 p. 2). This resonates with the model of entrainment proposed by Phillips-Silver et al (2010), according to whom entrainment is composed of three phases:…”
Section: When To Movesupporting
confidence: 75%
“…From the biomusicological point of view, entrainment is an organism's ability to synchronize movements in the presence of an external rhythmic stimulus. Thus, although music is the most studied and complex source of coordinated movements, entrainment is a very common biological occurrence that does not depend on music or musical rhythm only, but also transpires in a great number of acoustical and nonacoustical events (Phillips-Silver, Aktipis, & Bryant, 2010). Consequently, the synchronization required for interaction in musical environments must be considered as a particular case among various other forms of movement coordination found in musical and in nonmusical environments.…”
Section: Introductionmentioning
confidence: 99%
“…Penhune, Zatorre, & Evans, 1998;Phillips-Silver, Aktipis, & Bryant, 2010). Humans can match finger-taps to an auditory or a tactile metronome with equal fidelity (Elliott, Wing, & Welchman, 2010, and rhythmic vestibular input causes both adults and infants to interpret an ambiguously timed auditory beat as duple meter or triple meter (Phillips-Silver & Trainor, 2005, 2007Trainor et al, 2009).…”
Section: Beat-matching To Nonauditory Stimulimentioning
confidence: 99%
“…Hagen and Bryant (2003) showed that better temporal coordination in a music performance positively affected third party judgments of coalition quality between the musicians. While social entrainment may have evolved in many species from the simpler adaptive ability to entrain one's behavior to rhythmic information in the physical environment (Phillips-Silver et al, 2010), human interpersonal synchrony is moderated by many social factors and interacts in complex ways with group membership and the dynamics of alliance formation (Miles, Griffiths et al, 2009;Miles, Lumsden, et al, 2011 Laughter is another interactive phenomenon that can involve behavioral coordination and may be associated with cooperative behavior. Research has shown that people who have known each other longer tend to laugh together more (Bryant, 2012;Smoski & Bachorowski, 2003a) and familiarity between conversationalists is perceptible in the co-laughter itself (Bryant, 2012).…”
Section: B Copying a Behavior Of Individual A But With Neither A Parmentioning
confidence: 99%